Noise-to-signal transition of a Brownian particle in the cubic potential: I. general theory. (22nd April 2016) - Filip, Radim; Zemánek, Pavel
Abstract: The noise-to-signal transitions are very interesting processes in physics, as they might transform environmental noise to useful mechanical effects. We theoretically analyze stochastic noise-to-signal transition of overdamped Brownian motion of a particle in the cubic potential. The particle reaches thermal equilibrium with its environment in the quadratic potential which is suddenly swapped to the cubic potential. We predict a simultaneous increase of both the displacement and signal-to-noise ratio in the cubic potential for the position linearly powered by the temperature of the particle environment. The short-time analysis and numerical simulations fully confirm different dynamical regimes of this noise-to-signal transition.